Skin barrier homeostasis in atopic dermatitis: feedback regulation of kallikrein activity. - Reiko J Tanaka; Masahiro Ono; Heather A Harrington (PLoS ONE, 2011)
Atopic dermatitis (AD) is a widely spread cutaneous chronic disease characterised by sensitive reactions (eg. eczema) to normally innocuous elements. Although relatively little is understood about its underlying mechanisms due to its complexity, skin barrier dysfunction has been recognised as a key factor in the development of AD. Skin barrier homeostasis requires tight control of the activity of proteases, called kallikreins (KLKs), whose activity is regulated by a complex network of protein interactions that remains poorly understood despite its pathological importance. Characteristic symptoms of AD include the outbreak of inflammation triggered by external (eg. mechanical and chemical) stimulus and the persistence and aggravation of inflammation even if the initial stimulus disappears. These characteristic symptoms, together with some experimental data, suggest the presence of positive feedback regulation for KLK activity by inflammatory signals. We developed simple mathematical models for the KLK activation system to study the effects of feedback loops and carried out bifurcation analysis to investigate the model behaviours corresponding to inflammation caused by external stimulus. The model analysis confirmed that the hypothesised core model mechanisms capture the essence of inflammation outbreak by a defective skin barrier. Our models predicted the outbreaks of inflammation at weaker stimulus and its longer persistence in AD patients compared to healthy control. We also proposed a novel quantitative indicator for inflammation level by applying principal component analysis to microarray data. The model analysis reproduced qualitative AD characteristics revealed by this indicator. Our results strongly implicate the presence and importance of feedback mechanisms in KLK activity regulation. We further proposed future experiments that may provide informative data to enhance the system-level understanding on the regulatory mechanisms of skin barrier in AD and healthy individuals.